1991
DOI: 10.1111/j.1464-410x.1991.tb15101.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor Activity as a Marker in Transitional Cell Carcinoma of the Bladder

Abstract: An immunohistochemical staining method was used to study transferrin receptors (TFR) in bladder tissue from 10 patients with benign conditions and 33 with bladder cancer. All patients with bladder cancer were followed up by cystoscopy at intervals of 3 months (mean follow-up period 11 months). The relationship between TFR activity and recurrence rates was investigated. It was not possible to demonstrate TFR in normal bladder mucosa except for the proliferating cells of the basal layer. TFR activity in malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Expression of TfR on the cell surface is upregulated in several cancers, including breast cancer [36], bladder cancer [37], prostate cancer [38], leukemia and lymphoma [39]. Likely, this is the result of the increased requirement for iron of rapidly growing cells, since other proliferating cells also have high surface expression of TfR in comparison to their quiescent or slower-growing counterparts [39,40].…”
Section: Iron and Cancermentioning
confidence: 99%
“…Expression of TfR on the cell surface is upregulated in several cancers, including breast cancer [36], bladder cancer [37], prostate cancer [38], leukemia and lymphoma [39]. Likely, this is the result of the increased requirement for iron of rapidly growing cells, since other proliferating cells also have high surface expression of TfR in comparison to their quiescent or slower-growing counterparts [39,40].…”
Section: Iron and Cancermentioning
confidence: 99%
“…Immunohistological staining of ABO isoantigen [8], T-antigen [8], Tn-antigen [11], TFR [2,12], or other growth factor receptors [5] may be useful. However, histological grading alone does not always correlate with the clinical course of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, histological grading alone does not always correlate with the clinical course of the patients. Some investigators reported that TFR expression correlates well with histological grades using immunohistochemistry [2,12]. Because this method is a qualitative analysis, the results depend largely on examiners.…”
Section: Discussionmentioning
confidence: 99%
“…there are numerous examples of nuclear molecular imaging applications for the assessment of hormone and cell-surface receptor status (10,22,35,58). In the field of MRI, there have been attempts to monitor the expression levels of the transferrin receptor (tfR), which is linked to tumor grade and metastatic potential (9,32,67). the transferrin receptor is a cell-surface internalizing receptor responsible for almost all iron sequestration in mammalian cells.…”
Section: Molecularmentioning
confidence: 99%